2024
DOI: 10.3390/buildings14020497
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence and Optimization Design of Viscous Damper Parameters on the Damping Efficiency of Frame Shear Wall Structure

Xiang Lan,
Guanglan Wei,
Xingxian Zhang

Abstract: This study investigates the influence of viscous damper parameters on the damping efficiency of frame shear wall structures. Taking a specific frame shear wall structure as the background, a three-dimensional finite element model is established using a nonlinear dynamic time–history analysis method. The damping ratio, reduction in vertex displacement, reduction in base shear, and inter-story drift utilization rate are selected as the damping performance indicators. Firstly, a sensitivity analysis is conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The results indicated that when the intermediate column is located in the middle of the span, the displacement of the viscous damper is relatively large, and the inter-story displacement of the structure can be effectively controlled. Sonmez et al [36] adopted the artificial bee colony algorithm to determine the optimal placement of dampers in the structure; Bishop et al [37,38] adopted the genetic algorithm; and Lan et al [39] employed the response surface method. However, the increase in damper displacement caused by optimization is significantly smaller than the amplification effect caused by the amplification device.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that when the intermediate column is located in the middle of the span, the displacement of the viscous damper is relatively large, and the inter-story displacement of the structure can be effectively controlled. Sonmez et al [36] adopted the artificial bee colony algorithm to determine the optimal placement of dampers in the structure; Bishop et al [37,38] adopted the genetic algorithm; and Lan et al [39] employed the response surface method. However, the increase in damper displacement caused by optimization is significantly smaller than the amplification effect caused by the amplification device.…”
Section: Introductionmentioning
confidence: 99%